Mortality analysis of hospitalized trauma patients in the intensive care unit - Duran, Mehmet; Uludag, Öznur (Journal of Surgery and Medicine, 2020)
Aim: Trauma accounts for around five million deaths a year and constitutes a serious threat to public health globally. We examined the characteristics of patients admitted to the intensive care unit (ICU) due to trauma in 2015 and investigated the mortality rate and affecting factors. Methods: In this retrospective cohort study, the data of 101 trauma patients who were followed up at the general ICU in Adıyaman University Training and Research Hospital between January 2015 and December 2015 were analyzed. Patients’ demographic data, regions and causes of trauma, hospitalization durations, Glasgow Coma Scale (GCS) scores, whether blood products were transfused, mechanical ventilation support, operations, and duration of stay in ICU were noted. We then divided the patients into two groups as survivors and non-survivors and examined the mortality rates and the effective factors. Results: Mortality rates of the patients were 15.8%. The mean age of the patients included in the study was 30.73 (25.188) years. Among all, there were 71 males and 30 females. The most common causes of trauma were in-vehicle traffic accidents (33.7%), falls (28.7%) and extravehicular traffic accidents (24.8%). The patients were often admitted to the ICU because of head trauma. The ICU length of stay was significantly higher in the non-survivor group compared to the discharged group (12.81 (23.49) vs. 3.78 (2.84) days, P<0.001), along with the duration of mechanical ventilation (2.49 (8.85) vs. 0.74 (1.30), P<0.001). GCS scores at admission were significantly lower in the non-survivor group (5.88 (3.12) vs. 11.98 (2.70), P<0.001). Conclusion: Direct exposure to trauma as a pedestrian, duration of mechanic ventilation, and low GCS scores during admission increase mortality in patients admitted to the ICU due to trauma.